(3ceGd COH GdZfGAs - (3GdMSf Hf CMeO Hf Ydj GdcGJH, GdcGJH,J (B625 (3g` s ((3SfLGQ s)
(3ChdgG (B:s
(3GdMeO ddg ehdi GdfYe hGgd GdWhd hGdcQe dcd UfGYI ZGjI ef GdceGd hebOGQ ef GdefaYg Jchf Hg Jdc GdUfGYg Cced hCaVd s
(3BNQgG (B:s
(3aJQcg ai VdGdJg EP de jbHd efi , hGfJXQJ XghQ cJGHg dCVMc efg s
(3eQJH Ydi (B43 (3HGHGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B181s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B69 s
Keywords: (3GdehSjbi hGdZfGAs